Total and attuned multiple autonomy support and the social development of early adolescents - Simões, F. A. M. (2018)
The effects of Multiple Autonomy Support (MAS), meaning the autonomy support provided by two or more sources, is an overlooked topic in social development literature. The aim of this study is to understand how two types of MAS, Total Multiple Autonomy Support (TMAS) and Multiple Autonomy Support Attunement (MASA), are related to early adolescents’ social development indicators (prosocial behavior, self-regulation, antisocial behavior, alcohol use, and 1-year substance use intention). TMAS pertains to the general amount of autonomy support perceived by a MAS recipient, irrespectively of each provider’s contribution to that score. MASA refers to the interindividual patterns of perceived coordination among MAS providers, based on each provider’s autonomy scores. The participants were 818 early adolescent Portuguese (M?=?12.15; SD?=?.81; 54.2% girls) surveyed in a cross-sectional exploratory study about MAS provided by parents, teachers, and mentors. Descriptive analyses revealed levels of low (n? =?81; 10.00%), moderate (n? =?432; 52.82%), and high (n? =?302; 36.91%) TMAS. A k-cluster analysis revealed four MASA groups: low attuned MAS (n? =?128; 15.65), misattuned MAS/low attuned parent autonomy support (n? =?225; 27.51%), misattuned MAS/low attuned teacher autonomy support (n? =?177; 21.64%), and high attuned MAS (n? =?288; 32.21%). Ordinal regressions show that, after controlling for age, a pattern of high attuned MAS predicts better prospects of prosocial behavior and self-regulation, as opposed to high levels of TMAS. In addition, MASA involving low teacher autonomy support predicts the worst results on the selected indicators of social development.